Engineering electromagnetics - Hayt, William H. (McGraw-Hill, 2012)
First published just over 50 years ago and now in its Eighth Edition, Bill Hayt and John Buck’s Engineering Electromagnetics is a classic text that has been updated for electromagnetics education today. This widely-respected book stresses fundamental concepts and problem solving, and discusses the material in an understandable and readable way. Numerous illustrations and analogies are provided to aid the reader in grasping the difficult concepts. In addition, independent learning is facilitated by the presence of many examples and problems. Important updates and revisions have been included in this edition. One of the most significant is a new chapter on electromagnetic radiation and antennas. This chapter covers the basic principles of radiation, wire antennas, simple arrays, and transmit-receive systems.